The effects of addition of functional monomers and molecular imprinting on dual drug release from intraocular lens material - Topete, Ana (2022)
Although cataract surgery is considered a safe procedure, post-surgery complications such as endophthalmitis and ocular inflammation, may occur. To prevent this, antibiotics and anti-inflammatories are prescribed in the form of eye drops during the post-operatory period, but they lead to a low drug bioavailability in target tissues. The objective of this work is to develop an intraocular lens (IOL) material to deliver simultaneously one antibiotic, moxifloxacin (MXF), and one anti-inflammatory, diclofenac (DFN), in therapeutic concentrations to prevent both complications. The IOL material was modified through the incorporation of functional monomers, as well as molecular imprinting with both drugs using the same functional monomers, namely acrylic acid (AA), methacrylic acid (MAA), 4-vinylpiridine (4-VP) and a combination of MAA + 4-VP. The best results were obtained with MAA. Molecular imprinting did not influence the drug release, except with AA. Application of a mathematical model predicted that the released MXF and DFN concentrations would stay above the pre-determined MIC of S. aureus and S. epidermidis and the minimum values of IC50 of COX-1 and COX-2, for 9 and 14 days, respectively. Antibacterial tests showed that the released antibiotic remained active. The physical properties of the drug-loaded MAA-hydrogel remained adequate. The developed system proved to be non-irritant and non-cytotoxic.